Perception of unsafe driving behaviour and reported driving behaviour among commercial motorcyclists in Dar es Salaam, Tanzania. (October 2020) - Kiwango, George; Francis, Filbert; Hasselberg, Marie; Chillo, Omary; Moshiro, Candida
Highlights: Unsafe driving behaviours are prevalent among commercial motorcyclists. Commercial motorcycle drivers are aware of the involved risks of unsafe driving. Unsafe driving is associated with low perception of the dangers of unsafe driving. Abstract: Commercial motorcycle drivers are recognised to take high risks while driving, but little is known about their perception of these risks. This paper presents the results of a survey of 400 commercial motorcyclists' perception of unsafe driving behaviours and then determine the association between the perception of unsafe driving behaviour and reported driving behaviour. The study was carried out in Dar es Salaam between December 8th 2018 and March 24th 2019. Drivers aged 18 years and above were selected from 90 parking stages within the city and completed a structured interview. Modified Poisson regression was used to estimate the prevalence ratios (PRs). We found that close to 60% of drivers considered unsafe driving to be unsafe. However, reported unsafe driving behaviour was moderately common. Our results showed that reported unsafe driving behaviour (adjusted PR = 1.7; 95% CI 1.3–2.2) was associated with a low perception of the dangers of unsafe driving among motorcyclists. The higher the earnings a driver had (adjusted PR = 1.6; 95% CI 1.2–2.0), the higher the likelihood of having a low perceived risk of unsafe behaviour. These findings suggest that commercial motorcyclists' unsafe behaviour are, for the most part, not the result of a poor perception of the involved risks.